47, XXY Klinefelter syndrome: Clinical characteristics and age‐specific recommendations for medical management1. Issue 1 (23rd January 2013) - Aksglaede, Lise; Link, Katarina; Giwercman, Aleksander; Jørgensen, Niels; Skakkebæk, Niels E; Juul, Anders; Samango‐Sprouse, Carole A.; Gropman, Andrea L.
Abstract 47, XXY (Klinefelter syndrome) is the most frequent sex chromosomal disorder and affects approximately one in 660 newborn boys. The syndrome is characterized by varying degrees of cognitive, social, behavioral, and learning difficulties and in adulthood additionally primary testicular failure with small testes, hypergonadotropic hypogonadism, tall stature, and eunuchoid body proportions. The phenotype is variable ranging from "near‐normal" to a significantly affected individual. In addition, newborns with Klinefelter syndrome generally present with a normal male phenotype and the only consistent clinical finding in KS is small testes, that are most often not identified until after puberty. Decreased awareness of this syndrome among health professionals and a general perception that all patients with 47, XXY exhibit the classic textbook phenotype results in a highly under‐diagnosed condition with up to 75% of the patients left undetected. Typically, diagnosis is delayed with the majority of patients identified during fertility workup in adulthood, and only 10% of patients diagnosed prior to puberty. Early detection of this syndrome is recommended in order to offer treatment and intervention at the appropriate ages and stages of development for the purpose of preventing osteopenia/osteoporosis, metabolic syndrome, and other medical conditions related to hypogonadism and to the XXY as well as minimizing potential learning and psychosocial problems. The aim of this review is to present the clinical aspects of XXY and the age‐specific recommendations for medical management. © 2013 Wiley Periodicals, Inc.